'A Shared Future for Mankind': Rhetoric and Reality in Chinese Foreign Policy under Xi Jinping. Issue 133 (2nd January 2022) - Nathan, Andrew J.; Zhang, Boshu
ABSTRACT: The phrase 'work to build a community with a shared future for mankind' became the guiding slogan of Chinese foreign policy in 2017. Beneath its smooth surface, the concept contains several layers of complex and sometimes contradictory meanings. Among other things, it seeks to position China both as one among many developing countries, treating all as equals, and as a major world leader that exerts influence over other states and the international system. The concept is thus at once both egalitarian and hierarchical. Along with the core concept, Chinese foreign policy articulates niche discourses on ethno-cultural identity, Marxism, and human rights that are targeted at special audiences. The writings of leading Chinese international-relations intellectuals tend to reveal a more emphatically hierarchical view of the international system, with China at the top, than is explicit in China's official rhetoric. Xi's international message has been promoted energetically by domestic media and promoted tirelessly on the international stage, with adaptations appropriate to diverse audiences. The Chinese message has met with a mixed reception abroad. China's rhetoric of cooperation is seen by many in other countries as a cover for self-interested strategic motives.